Factors Influencing Medication Adherence in Patients with Type 2 Diabetes Mellitus in Japan - Emira Ramadhany, Nuzla; Olivia, Viona; Putri, Nabila Azzahra; Yuwono, Brian Jordan; Oktharina, Eka Handayani; Nurwany, Raissa (Biomedical Journal of Indonesia, 2025)
Introduction. Diabetes mellitus (DM) is a chronic metabolic disease marked by persistent hyperglicemia. Type 2 diabetes mellitus (T2DM) is increasingly prevalent in Japan, affecting approximately 10% of adults with diabetes, according to the Ministry of Health, Labor and Welfare in 2020. Maintaining medication adherence is critical for T2DM management and complications prevention. This review aimed to synthesize factors influencing medication adherence in T2DM patients in Japan. Methods. This systematic review followed PRISMA-P guidelines, using the keywords The keywords “risk factors", "medication adherence", "diabetes mellitus", and "Japan”. After applying inclusion and exclusion criteria, five cross-sectional studies were selected for analysis. Results. Medication adherence among Japanese T2DM patients ranged from 65% to 85%. Positive factors linked to higher adherence included higher family income, knowledge of drug effect, absence of complication, increased number of medications, frequent healthcare utilization, structured lifestyle perception, and physical functionality. In contrast, variables such as gender, education level, and type of medication showed no significant influence in multiple studies. The use of validated scales highlighted correlations between high adherence and improved HbA1c outcomes. Conclusion. Medication adherence is multifactorial, driven by clinical and socio-behavioral determinants. Knowledge and perception-based interventions, combined with lifestyle modification and simplified therapy regimens, may enhance adherence in Japanese T2DM patients.